Revisitando la idea / el ideal de la Sociedad Civil Global a la luz de los Derechos Humanos - Andrés López Rivera (Universidad Hemisferios, 2016)
In the past few decades, the proliferation of a “third sector” of nongovernmental and non-profit organizations that operate across borders has prompted a reformulation of the concept of civil society. A number of contemporary studies contend that the previously state-centric civil society is becoming international, transnational or global. Whether the emergence of an autonomous realm of world citizens is merely a projection of a cosmopolitan ideal or a real phenomenon is a contentious issue. The present article problematizes the idea of a global civil society by analysing its descriptive purchase and its normative implications. Drawing on a constructivist approach, the paper proposes the term “ideational infrastructure” to analyse its discursive and interpretive underpinnings. The analysis finds that global civil society is a reification rooted in human rights discourse as a contemporary ideal and a moral aspiration.